Community-acquired methicillin-resistant Staphylococcus aureus: a growing public health problem. Issue 1 (October 2007) - Purcell, Kevin; Fergie, Jaime
Community-acquired methicillin-resistant Staphylococcus aureus (CAMRSA) infections slowly began to be reported in healthy children from the late 1980s through to the late 1990s. Since 2000, many investigators have described rapid increases in the number of children that are colonized and infected with CAMRSA. Initially, most children presented with localized skin and soft-tissue infections (e.g., cellulitis, abscesses, furuncles and carbuncles). However, more children are now having severe invasive infections, including overwhelming sepsis with deep venous thrombosis, necrotizing pneumonia, empyema, multifocal osteomyelitis, septic arthritis, pyomyositis, necrotizing fasciitis, orbital and pre-septal cellulitis, toxic shock syndrome and endocarditis. Similar invasive infections are also now being seen with community-acquired methcillin-susceptible S. aureus (CAMSSA) and the relative virulence of CAMRSA strains compared with CAMSSA strains is unclear and may be changing. The emergence of CAMRSA has required a change in empiric antibiotic therapy away from penicillins and cephalosporins to assure appropriate coverage. Although many recommendations have been made for controling the spread of CAMRSA and decolonizing patients, there is little evidence to support the effectiveness of these practices. We will be limited in our ability to prevent these infections unless an effective S.  aureus vaccine is developed.